DIVERSIFIKASI PRODUK PERIKANAN DI DESA PESISIR MELALUI PEMBUATAN ABON IKAN SELAR TETENGKEK (MEGALASPIS CORDYLA) DI KELURAHAN BANTEN KECAMATAN KASEMEN - Sri Lestari Handayani; Aliza Zaharani (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Banten Village is a coastal area that has historically and functionally been the center of capture fisheries activities in Serang City. The fundamental problem faced by the coastal communities of Banten Village is their high dependence on fresh fish sales. In general, most of the fish catch is sold directly to middlemen or fish traders, and only a few fishermen increase the added value through fish processing or product diversification. Diversification of fishery products through fish floss processing is an effort to increase the added value of marine products while encouraging the community to be able to produce, package, and market processed fish products independently. The method used is Participatory Action Research (PAR). The results show that the community service program through the development of marine products in the form of iBON (Fish Floss) implemented by the Thematic KKM Group 43 of Sultan Ageng Tirtayasa University in Banten Village, Kasemen District, Serang City, has succeeded in becoming a form of coastal community empowerment based on local potential. Socialization activities, demonstrations, and hands-on practice in making fish floss can improve the knowledge and skills of the community, particularly housewives, in processing seafood into hygienic, economically valuable, and long-lasting processed food products. Keywords: Diversification; Fish Floss; Banten Village